A comprehensive review of different approaches used by manufacturing industries in handling capacity planning under demand uncertainties - Yahaya, Saifudin Hafiz; Salleh, Mohd Shukor; Ang, Chew Woon; Cahyadi, Novi (Semarak Ilmu Publishing, 2024)
In today's dynamic industrial environment, efficient capacity planning is of essential relevance, especially in the face of unpredictable and fluctuating client demands. Failure to address demand uncertainty may lead to undesirable effects, such as overproduction or underproduction. This study carefully analyses variety of capacity planning approaches employed by the industry. Additionally, the research extended to explore several simulation approaches employed as powerful tool in tackling capacity planning issues, delivering adaptable solutions that respond to the particular demands of both major organizations and small to medium-sized firms. This analysis underlines the vital role of simulation in increasing operational performance, optimizing resource allocation, and reacting to changing production needs, eventually leading to greater competitiveness and efficiency within the manufacturing industry.